As crónicas de Zurara: a corte, a aristocracia e a ideologia cavaleiresca em Portugal no século XV - Miguel Aguiar (Medievalista)
This article aims to analyse Gomes Eanes de Zurara’s chronicles, considering not only form and style, but also the message regarding the general purposes of the text. Chronicles were seen as “nobles' mirrors” based on chivalric principles, which functioned as a way of shaping aristocracy’s behaviour, while simultaneously defining the competitivity amid that social group. Nonetheless, these texts can also be analysed as pieces of ‘propaganda’ on behalf of the crusade in North Africa, validating and reinforcing internally and externally the zeal and eagerness of this same movement.